CAVEAT EMPTOR VERSUS KHIYAR AL-'AYB - Muhammad Ma'sum Billah (International Institute of Islamic Thought, 1997)
It is an obligation in any commercial (sale-purchase) transaction that prior to entering into an agreement, the seller is to allow the buyer to inspect the goods, in order to ensure that they are free from any unknown defect. Such an obligation on the seller is known in common law as caveat emptor.' The doctrine, in other words, gives the buyer a right to determine whether the goods to be purchased are free from any defect before the actual agreement is completed, so as to protect him from any future risk from a defective product. Thus, this doctrine implies that the buyer, after such inspection or investigation of the fitness of such goods, will shoulder the responsibility of any risk on the goods after the conclusion of the said sale and purchase agreement. Jowitt's Dictionary of English Law explains that a buyer must be on the alert, for he has no right to remain in ignorance of the fact that what he is buying belongs to someone other than the vendor and that any buyer who fails to investigate the vendor's title does so at his own risk. However, caveat emptor does not imply any obligation on the seller to point out a defect in the goods to be sold.3 He is, therefore, only obliged to allow the buyer or purchaser to investigate the goods himself and nothing more. The buyer, in h s case, can decide before any sale and purchase agreement whether to carry out such an inspection on the goods to be sold. The buyer is then at liberty whether to exercise this means of protection against any defective goods! Islamic law also provides such a safeguard against any defective products or goods in a sale and purchase agreement. The Islamic doctrine which allows such safeguard is called in Islamic commercial terminology khiyur al-'ayh. Thus, under Islamic commercial law, the seller, in a sale and purchase agreement, is ...